2017
DOI: 10.1007/s13204-017-0625-4
|View full text |Cite
|
Sign up to set email alerts
|

Gd–Bi–Ce–O materials as catalysts in CO oxidation

Abstract: Ceria-based solid solutions doped by Gd and/or Bi were synthesized by co-precipitation method from acid aqueous solution of cerium, gadolinium, and bismuth salts, followed by calcination at the temperature of 500°C. Characterization of the synthesized samples by many methods was carried out. It is shown that all obtained powders of solid solutions crystallized into a cubic structure of the fluorite type, with an average particle size of 10-17 nm, and for the sample obtained through intermediate acetylacetonate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…No micropores (< 2 nm, according to t-plot method) were observed in all samples, and no regularity in the change of Cu / Mn ratio was too. Unfortunately, this method did not allow creating narrow monomodal pore size distribution as in our earlier work [13,14], but it may be done by using acetylacetone. Table 1).…”
Section: Resultsmentioning
confidence: 96%
“…No micropores (< 2 nm, according to t-plot method) were observed in all samples, and no regularity in the change of Cu / Mn ratio was too. Unfortunately, this method did not allow creating narrow monomodal pore size distribution as in our earlier work [13,14], but it may be done by using acetylacetone. Table 1).…”
Section: Resultsmentioning
confidence: 96%
“…In literature, various types of catalysts have been investigated for CO oxidation reaction in which particularly platinum group metals based catalysts show very high activity . Recently, Zagaynov reported the catalytic behavior of Bi and Gd doped CeO 2 compounds for CO oxidation reaction and found that Bi doped CeO 2 shown higher catalytic activity compared to Gd doped CeO 2 . In our studies we have tested Bi doped in La 2 O 3 compounds for the same reaction.…”
Section: Introductionmentioning
confidence: 99%